1982
DOI: 10.1093/ajcp/77.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced Changes in Common Laboratory Tests

Abstract: Examination of 19 serum biochemical and hematologic parameters in a group of white male runners, ranging in age from 23 to 47 years, just prior to and immediately after a 13-mile "mini-marathon," demonstrated a significant increase, by paired Student t-test, in mean values of: K+, BUN, creatinine, CK, LDH, AST (SGOT), alkaline phosphatase, bilirubin, uric acid and leukocyte counts. Prevailing environmental conditions were such as to produce no significant hemoconcentration. Using this group's statistics and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
2
2

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 30 publications
6
21
2
2
Order By: Relevance
“…CK and LDH isoenzymes are muscle injury biomarkers (25). Some studies have shown changes in muscle enzymes and isoenzymes serum concentrations after intense training in athletes and untrained subjects (26,27). Increased CK activity may be due to metabolic and mechanical causes.…”
Section: Discussionmentioning
confidence: 99%
“…CK and LDH isoenzymes are muscle injury biomarkers (25). Some studies have shown changes in muscle enzymes and isoenzymes serum concentrations after intense training in athletes and untrained subjects (26,27). Increased CK activity may be due to metabolic and mechanical causes.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of total LDH and its isoenzymes allows obtaining much information about the muscle metabolism [4]. In fact strenuous exercise induces a significant increase of LDH [31] and the degree of the rise depends on the intensity and duration of the effort [32,33]. We did not found an increase of total enzyme in Group A, neither in Group B, in both tests (C and H), probably for the type and intensity of effort: In our study the time of examination (30 minutes after exercise) and the type of exercise (submaximal) did not allow to detect a significant increase of total enzyme (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…El límite sobre el nivel de intensidad por el cual el musculo puede soportar es el punto de equilibrio: cuando la carga excede un cierto límite, la creatina quinasa (CK) y otras enzimas proteicas como la lactato de hidrogenasa (LDH), se liberan hacia el fluido intersticial y son absorbidas a través del sistema linfático, retornando de esta manera al flujo sanguíneo (Bijsterbosch y col., 1985). La LDH es inducida por el ejercicio, y el grado de su incremento dependerá de la intensidad y la duración del esfuerzo (Priest, Oei, Moorehead, 1982;Munjal, McFadden, Matix, Coffman, Cattaneo, 1983;Stokke, 1982). Se ha observado un importante incremento de LDH entre el L Vilamitjana, J.; Vaccari, J. C.; Toedtli, M.; Navone, D.; Rodríguez-Buteler, J. M.; Verde, P. E., y CallejaGonzález, J.…”
Section: Introductionunclassified